Phytoplankton dynamics in the North American Great Lakes - Munawar, M.; Munawar, Iftekhar Fatima (Burlington, Ontario, Canada : Aquatic Ecosystem Health and Management Society, 2014)
Phytoplankton Dynamics in the North American Great Lakes is the compilation of two volumes, originally published 1996 and 2000. Both volumes provide a thorough treatment of the community structure, function, and dynamics of phytoplankton in the North American Great Lakes and represent the culmination of nearly three decades' worth of work by Mohiuddin Munawar and Iftekhar F. Munawar. With these volumes, the phycology of the North American Great Lakes has been brought into the new millennium. Volume 1 focuses on the Lower Great Lakes-Lakes Ontario and Erie-while volume 2 highlights Lakes Mich.
v. 1. Lakes Ontario, Erie and St. Clair -- v. 2. Lakes Superior and Michigan, North Channel, Georgian Bay and Lake Huron.
Includes bibliographical references and index.
Online resource; title from PDF title page (ebrary, viewed March 18, 2015).
eBooks on EBSCOhost
Keywords: Phytoplankton -- Great Lakes (North America); Aquatic ecology -- Great Lakes (North America); Water quality -- Great Lakes (North America); Water -- Pollution -- Great Lakes (North America); Phytoplancton -- Grands Lacs (Amérique du Nord); Eau -- Qualité -- Grands Lacs (Amérique du Nord); SCIENCE -- Life Sciences -- Biology; SCIENCE -- Life Sciences -- Microbiology; Aquatic ecology; Phytoplankton; Water -- Pollution; Water quality; Great Lakes